2014
DOI: 10.1111/pirs.12044
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing regional business change at plant level in Italy: A novel spatial shift‐share approach

Abstract: In this paper, spatial shift-share decomposition is analysed when applied to Italian data on regional business change at plant level, over the period [2004][2005][2006][2007][2008][2009]. A new type of spatial decomposition, which looks more effectively at neighbourhood influence, is introduced here. Notable results emerge from the empirical investigation. First, it can be seen that the spatial level of aggregation greatly affects results. Second, evidence of neighbourhood advantage in the Southern NUTS 3 regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 21 publications
3
40
0
Order By: Relevance
“…So they are less affected because their regional economies are not integrated into the national economy. These results are also in agreement with those in Espa et al (), even though in this case businesses are classified by two dimensions only (spatial and sectoral) over the period 2004–2009. Espa et al () attribute the higher rates of business change recorded in Southern regions to the smaller impact of the crisis on relatively less developed regional economies.…”
Section: Datasupporting
confidence: 93%
See 1 more Smart Citation
“…So they are less affected because their regional economies are not integrated into the national economy. These results are also in agreement with those in Espa et al (), even though in this case businesses are classified by two dimensions only (spatial and sectoral) over the period 2004–2009. Espa et al () attribute the higher rates of business change recorded in Southern regions to the smaller impact of the crisis on relatively less developed regional economies.…”
Section: Datasupporting
confidence: 93%
“…So they are less affected because their regional economies are not integrated into the national economy. These results are also in agreement with those in Espa et al (2014) change recorded in Southern regions to the smaller impact of the crisis on relatively less developed regional economies. These aspects are further investigated in the fourth section.…”
Section: Datasupporting
confidence: 90%
“…It measures the effect of changes in the electricity intensities of various sectors during the study period. The equation is as follows [21,22]:…”
Section: Methodsmentioning
confidence: 99%
“…Following Nazara and Hewings' idea, Zaccomer [20] developed SSS into a complete model. Subsequently, Espa et al [21] suggested a spatial shift-share decomposition of regional business changes at the plant level in Italy. Grossi and Mussini [22] recently applied SSS to explore the changes in regional electricity consumption across Italy over the period 2000-2013.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if the neighbourhood effect shows a positive value but the difference in performance between neighbours and nation is negative, the advantage of the region r is mainly due to individual factors rather than to neighbourhood influence. In order to overcome such a drawback, Espa et al () introduced a novel type of spatial decomposition built on four simple effects. Specifically, they decompose the second term of equation (3) into two simple effects as follows: true(truegirgntrue)=true(truegirgintrue)+true(gingntrue) …”
Section: Measuring Firm Demography Changementioning
confidence: 99%